2010
DOI: 10.1029/2009jd012557
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of the local interstellar spectrum for the solar modulation parameter

Abstract: [1] Cosmogenic Isotopes are produced in the Earth's atmosphere due to the interaction of galactic cosmic rays with nuclei of atmospheric atoms. Among others, the 10 Be concentration in ice cores depends on the galactic cosmic ray flux outside of the Earth's magnetosphere and provides therefore a unique tool to investigate the solar modulation over very long time periods. In this study we investigate the importance of different local interstellar proton spectra often used in literature obtained outside of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 39 publications
3
96
0
Order By: Relevance
“…For further comparison, the LIS given by Webber & Higbie (2009;WH09 hereafter) is included in the plots. We used the parametrization given in Herbst et al (2010), where a comparison between a few proposed LIS can be found as well. In face of the still imprecisely known modulation effects on measured spectra inside the heliosphere (see, e.g., Florinski et al 2011;Scherer et al 2011), such an LIS parametrization can give only a rough orientation for what to expect for Galactic CR propagation studies.…”
Section: The Resulting Spatial and Spectral Cr Distributionmentioning
confidence: 99%
“…For further comparison, the LIS given by Webber & Higbie (2009;WH09 hereafter) is included in the plots. We used the parametrization given in Herbst et al (2010), where a comparison between a few proposed LIS can be found as well. In face of the still imprecisely known modulation effects on measured spectra inside the heliosphere (see, e.g., Florinski et al 2011;Scherer et al 2011), such an LIS parametrization can give only a rough orientation for what to expect for Galactic CR propagation studies.…”
Section: The Resulting Spatial and Spectral Cr Distributionmentioning
confidence: 99%
“…The exact value of the modulation potential is not important since it can be defined only relatively, depending on the primary assumption on the local interstellar spectrum (LIS) so that the same GCR spectrum near Earth can be parametrized by different values of φ for different LIS assumptions (Usoskin et al 2005;Herbst et al 2010). However, once the LIS is fixed, the value of φ unambiguously determines the GCR energy spectrum.…”
Section: The Heliospheric Modulation Potentialmentioning
confidence: 99%
“…Nevertheless, the true LIS is still far from conclusive [Webber et al, 2013]. In addition, different LIS models can produce the observed spectrum with LIS model-dependent modulation parameters [Herbst et al, 2010]. Furthermore, recent studies show that remarkable modulation exists in the outer heliosphere and even beyond the heliopause [e.g., Scherer et al, 2011;Strauss et al, 2013].…”
Section: Modulation Modelmentioning
confidence: 99%